KAJIAN FURNITURE PADA RUMAH HUNIAN KOLONIAL BELANDA - Irena Vanessa Gunawan; Citra Amelia (Ide dan Dialog Desain Indonesia (Idealog), 2018)
The era of Colonization in Indonesia left many architecture and interior influence. For many years, colonizers especially Dutch and English have developed many architectural building which included their interior elements. Bandung, is one of the cities which enjoyed massive influence of Dutch colonialism design. However the change of people way of living and conducting business, change the city area planning. Most of residential areas now have becoming commercial/business area. Houses area are being leased or sold to be transformed into offices, cafes, restaurant or being entirely demolished into new buildings. There are still residential buildings from this era which are being kept as it is.Either by the owner and endorsed by the appeals of communities intended to preserve them as historical buildings. However there are not yet efforts to preserve the interior elements, especially the furnitures. Hence there are little knowledge about the development of furnitur design as a result of living culture of this period. The ones left are difficult to study as furnituer has shorter life span than building so it could be already altered, moved or sold. And in the meantime new furnitures could be acquired.Hence, it is the intention of this research to study what is left of furnitur from colonialization era in this paticular residential house. To try to documents and analyze what style and influence the commonly called â€œDutch Furnitureâ€ by Indonesian antique dealers and also by the people in general.. This research will try to find out how and why this particular style still exist through the colonialism era in Indonesia to be compared to the development of styles in the European world.